Pressure ulcers – risk assessement and prevention - Sopata, Maciej; Tomaszewska, Elżbieta; Głowacka, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2007)
Pressure ulcers are a serious problem in chronic immobile patients. They are very often a cause of additional complications and serious costs. The assessment of risk factors and proper prophylactics play the key role in the battle with this complications. In this paper we present basic knowledge concerning the risk assessment of pressure ulcer formation and modern methods of prevention.